PENGARUH FOOD QUALITY, PRICE, LOCATION AND ENVIRONMENTDAN SERVICE QUALITY TERHADAP CUSTOMER LOYALTY MELALUI CUSTOMER SATISFACTION - Asri KURNIASARI ARIFIN; Wibisono Soediono (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2021)
This study aims to determine the effect of food quality, price, location and environment, service quality on customer loyalty through customer satisfaction at Mc Donald's in Bekasi City. The sampling technique used in this research is non-probability sampling with purposive sampling method and the sample size is 150 respondents. Respondents are domiciled in Bekasi City and are McDonald's customers in Bekasi City with a minimum requirement of having purchased and used Mc Donald's services in Bekasi City twice or more in the past month. The data in this study will be analyzed using Partial Least Square (PLS) with WarpPLS software version 7.0. The results of this study indicate that food quality, price, location and environment, service quality have a positive and significant effect on customer satisfaction, and there is a positive and significant influence between customer satisfaction and customer loyalty at McDonald's restaurants in Bekasi city.